Factors That Determined University Selection (Case Study on High School/Vocational High School Students in Sidoarjo) - Hadi Cahyono; Atikah Aghdhi Pratiwi (LPPM of NAROTAMA UNIVERSITY, 2018)
Competition between universities in attracting prospective students is now getting tighter, the competition that occurs today is not only applicable among private universities, but it seems that state universities also enliven the arena of prospective student selection. This phenomenon is getting stronger since the status of several State Universities was changed to become a Legal Entity State University (PTN-BH), where one of the implications is that more programs and acceptance channels are opened for prospective students who want to enter State University. The focus of this study explores what factors will determine a high school / vocational high school student choosing a university, especially a private university. The results of this study are expected to be used as a reference for private universities, especially departments that have marketing functions at the University to increase the number of prospective students who register. Data was collected through the process of distributing questionnaires given to 12th grade high school / vocational high school students in the Sidoarjo region. Researchers hope that through this research can be obtained a picture that can be used by the university in determining the strategy for the Sidoarjo region. The result of this study indicate that the variables that influence the selection of Private Universities in Sidoarjo. Accidental sampling was used to collecting data because the population is unknown, where questionnaires is given to 412 high school and vocational high school students in Sidoarjo for three weeks period. The results of this study indicate that the variables that influence the selection of Private Universities in Sidoarjo are Product (X1), People (X5), Process (X6) and Physical Evidence (X7).